Mobile phone call reminders to improve oral rehydration salt and zinc adherence for acute diarrhea in children: a single-center, randomized controlled trial - Titilayo Funmilayo Kayode-Alabi; Rasheedat Mobolaji Ibraheem; Kayode Olusegun Alabi; Aishat Oluwatoyin Bolakale; Samuel Kolade Ernest (BMC, 2024)
Abstract Background Low-osmolarity oral rehydration salt (ORS) and zinc therapy effectively manage diarrhea in children under five years of age, offering both short- and long-term benefits. Despite this, caregivers' adherence to ORS and zinc is often unsatisfactory due to factors such as forgetfulness, resolution of symptoms, and underestimation of the disease's severity. This study assessed the effect of mobile call reminders on ORS and zinc tablet adherence among children with acute diarrhea in a secondary-level health facility in Kwara State, Nigeria. Methods Using an open-label, randomized controlled trial design, this study compared caregiver-child pairs with acute diarrhea aged 6-59 months who received standard instructions (SI) alone (control group) and an intervention group (IG) who received SI plus phone call reminders on days three and seven of zinc sulfate therapy. All participants used a pictorial diary to track loose/watery stools and ORS and zinc tablet treatments for ten days. The primary outcome measures were independent and combined adherence to ORS and zinc therapy. The secondary outcomes were independent and combined adherence scores, defined as the percentage of times the ORS was given post-diarrhea and the percentage of prescribed zinc tablets administered out of ten. Results A total of 364/400 mother-child pairs completed the study. The percentage of mothers with full adherence in the intervention group was 82.5% for ORS, 72.1% for zinc, and 58.5% for combined use, compared to 78.8%, 60.8%, and 43.6%, respectively, in the control group. The odds of full adherence to ORS and zinc were 1.6 and 1.7 times higher among intervention mothers [ORS: OR = 1.561, 95% CI = 0.939-2.598, P = 0.085; zinc: OR = 1.671, 95% CI = 1.076-2.593, P = 0.022], and 1.8 times higher for combined use according to WHO guidelines [OR = 1.818, 95% CI = 1.200-2.754, P = 0.005]. The mean adherence scores for the intervention group were higher than those for the control group by 4.1% (95% CI = 0.60-7.60) for ORS, 7.3% (95% CI = 3.74-10.86) for zinc, and 5.7% (95% CI = 3.23-8.17) for the combined treatment. Conclusion Phone reminders can effectively improve consistency of home treatment administered by caregivers for children under five years old. Trial Registration The study was registered retrospectively (17/3/2023) with the Pan African Clinical Trial Registry (PACTR202301560735856).